THE IMPACT OF CLIMATE CHANGE ON THE BIODIVERSITY OF PROTECTED AREAS AND ITS IMPLICATIONS FOR THE ECONOMY OF PROTECTED AREAS - VOIEVODA, VOLODYMYR; SOVHIRA, SVITLAVA; DARMOFAL, ELEONORA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Biodiversity is the basis of ecosystem stability and regeneration of natural resources. The trend of increasing anthropogenic pressure on the natural environment and global climate dynamics negatively affect biodiversity, leading to the narrowing of natural biotopes and population reduction. Particularly representative in this context are the territories of the nature reserve fund (NRF), which provide unique prerequisites for the conservation of endangered and rare species. The aim of the article is to analyze the aspects of the impact of climate change on the biodiversity of protected areas and the consequences for the economic development of NRF objects. The study considers the main consequences of global climate change for ecosystems. The dynamics of biodiversity of protected areas due to global warming are determined. Priority approaches to the regeneration of populations in reserve ecosystems during the implementation of climate change programs have been identified, including improving the regulatory framework, optimizing environmental impact assessment procedures, integrating projects for the protection and use of natural resources and increasing species resilience, and engaging in international initiatives to reduce greenhouse gas emissions and stabilize climate processes. It has been established that changes in biodiversity under the pressure of climate dynamics can have a significant impact on the economy of protected areas in the context of reducing tourist attractiveness, reducing income from ecosystem services (carbon absorption, water balance regulation, etc.), increasing costs for adaptation and management, and complicating the support of endangered species. It has been substantiated that the expansion of the ecological network is fundamental for the effective regeneration of natural resources and the preservation of biodiversity.